The Concept of Permeability on The Neighbourhood Scale - Urrohmah, Aulia; Ellisa, Evawani; Fuad, Achmad Hery (UI Scholars Hub, 2023)
Urban sprawl is rapidly expanding in the outskirts of Jakarta, resulting in a patchwork of urban areas. Unlike many walkable cities in Europe that have long embraced the pedestrian culture, Jakarta and other developing cities have prioritized private vehicle-oriented development, leading to mixed urban forms. According to data from BPS in 2022, over 16.5 million motorcycles are registered in Jakarta, and 62.3% of Jabodetabek commuters use them. This study recognizes the permeability of neighbourhood scale concerning using motorcycles to support daily mobility. This narrative qualitative research investigated permeability regarding the legibility, variety, and perceptual aspects. In addition, to illustrate the potential of motorcycles, this case study explores the concept of permeability at the neighborhood scale, highlighting the role of motorcycles in supporting it. The findings show that the permeability on neighbourhood scale relates to the negotiation space between motorcycles mobility and residents, including street vendors. Despite the significant impact of motorcycles on the city's configuration, stakeholders involved in urban space interventions have yet to fully recognize the importance of addressing motorcycle-related issues, including safety and livability.